LEUKOPENIA AS THE ONLY SYMPTOM OF COVID-19 IN PATIENTS WITH SCHIZOPHRENIA ON CLOZAPINETHERAPY - Greš, Alen; Staver, Dijana; Sagud, Marina (Engrami, 2022)
Patients suffering from Covid-19 often have leukopenia, most often lymphopenia, as an accompanying laboratory manifestation of the clinical syndrome, but there are indications that at the beginning of the disease they also have mild neutropenia. Clozapine can have hematological side effects in terms of leukopenia - most often neutropenia. The paper presents a patient with schizophrenia who is on long-term clozapine therapy. At the time when leukopenia was detected in the blood count, he was mentally stable and physically asymptomatic. He had a reduced number of leukocytes as the only symptom of infection with the new coronavirus SARS CoV 2, which we confirmed by PCR. In this paper, we present the clinical picture of Covid-19 in connection with the possible overlapping etiology of leukopenia, which can also appear as a separate symptom of infection with the SARS CoV 2 coronavirus and be a hematological side effect of clozapine treatment.